2011
DOI: 10.1080/21567069.2011.586679
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate paramedic students’ attitudes to e-learning: findings from five university programs

Abstract: Computers and computer-assisted instruction are being used with increasing frequency in the area of undergraduate paramedic education. Paramedic students' attitudes towards the use of e-learning technology and computer-assisted instruction have received limited attention in the empirical literature to date. The objective of this study was to determine paramedic students' attitudes towards e-learning. A cross-sectional methodology was used in the form of a paperbased survey to elicit students' attitudes to e-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
(11 reference statements)
0
11
0
Order By: Relevance
“…Fact: There is no evidence of a pent-up demand for online learning While some have proposed that those in the rising ''Net Generation'' have greater expectations for online instruction (Sandars & Morrison 2007), recent evidence suggests that age cohort has less influence than predicted (Bennett & Maton 2010;Jones et al 2010;Margaryan et al 2011) and that students might prefer to use computers less than they currently do (Williams et al 2011). A recent comprehensive review Improving the value of online learning (Jones & Shao 2011) concluded that although younger students often have more experience using the newest technologies, there is not a natural demand for new technologies in their learning activities, and that the relationship amongst teachers, students and technology ''is determined by the requirements teachers place upon their students to make use of new technologies and the way teachers integrate new technologies in their courses''.…”
Section: Myth 5 the ''Net Generation'' Wants Online Learningmentioning
confidence: 99%
“…Fact: There is no evidence of a pent-up demand for online learning While some have proposed that those in the rising ''Net Generation'' have greater expectations for online instruction (Sandars & Morrison 2007), recent evidence suggests that age cohort has less influence than predicted (Bennett & Maton 2010;Jones et al 2010;Margaryan et al 2011) and that students might prefer to use computers less than they currently do (Williams et al 2011). A recent comprehensive review Improving the value of online learning (Jones & Shao 2011) concluded that although younger students often have more experience using the newest technologies, there is not a natural demand for new technologies in their learning activities, and that the relationship amongst teachers, students and technology ''is determined by the requirements teachers place upon their students to make use of new technologies and the way teachers integrate new technologies in their courses''.…”
Section: Myth 5 the ''Net Generation'' Wants Online Learningmentioning
confidence: 99%
“…Currently, these two models still exist for paramedic education; however, the former model is being progressively phased out of the system with the national trend in paramedic education moving towards pre‐employment tertiary programmes as a model that will become the sole point of entry to the profession in the future. Entry‐level paramedic qualifications are offered today in 14 higher education institutions . Also on offer at some Australian universities is a full range of courses from undergraduate bachelor degree level programmes through to postgraduate courses at both masters and PhD levels.…”
Section: Introductionmentioning
confidence: 99%
“…Graduates employed in this capacity are eligible for membership with Paramedics Australasia and/or the Australian Registry of Emergency Medical Technicians (AREMT). Yet, despite these very practical requirements, the ability to practice practical skills in the programs can be limited for many of the students, who study the program at a distance (Williams et al, 2011).…”
Section: Background Problemmentioning
confidence: 99%
“…In health education, simulation can assist with student skills , especially in task training (Wickens, Hutchins, Carolan, & Cumming, 2013). Given that paramedic science is seeing a shift away from face-toface lectures towards blended learning and distance education (Williams et al, 2011), this presents an opportunity to explore methods to provide simulation task training to distance education students.…”
Section: Introductionmentioning
confidence: 99%